2008
DOI: 10.1186/1753-4631-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Force plate monitoring of human hemodynamics

Abstract: Background: Noninvasive recording of movements caused by the heartbeat and the blood circulation is known as ballistocardiography. Several studies have shown the capability of a force plate to detect cardiac activity in the human body. The aim of this paper is to present a new method based on differential geometry of curves to handle multivariate time series obtained by ballistocardiographic force plate measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…PDA presents the extension of the findings of a number of studies that have utilized ballistocardiography and invasive central artery manometers to track mechanical events such as heart contractions and pressure pulse reflections in the central arterial tree, to the arterial periphery. These studies [ 17 - 19 ] have confirmed the existence of two major reflection sites in the central arteries. The first reflection site is the juncture between thoracic and abdominal aorta, which is marked by a significant decrease in diameter and a change in elasticity and the second site arises from the juncture between abdominal aorta and common iliac arteries.…”
Section: Introductionmentioning
confidence: 81%
“…PDA presents the extension of the findings of a number of studies that have utilized ballistocardiography and invasive central artery manometers to track mechanical events such as heart contractions and pressure pulse reflections in the central arterial tree, to the arterial periphery. These studies [ 17 - 19 ] have confirmed the existence of two major reflection sites in the central arteries. The first reflection site is the juncture between thoracic and abdominal aorta, which is marked by a significant decrease in diameter and a change in elasticity and the second site arises from the juncture between abdominal aorta and common iliac arteries.…”
Section: Introductionmentioning
confidence: 81%
“…One of the CT device’s central practical benefits is the comfortable data acquisition using the finger cuff, increasing potential ease of use and patient comfort. The unique feature for the device is the PDA model that is based on a concrete physical model that explains the structure of the peripheral arterial pressure pulse due to central arterial reflection sites [ 3 , 6 ]. In addition to monitoring blood pressure, modeling the superposition of the component pulses makes it possible to explain and predict otherwise confounding pulse envelope changes.…”
Section: Discussionmentioning
confidence: 99%
“…The CT measures continuous noninvasive blood pressure via a pulse contour analysis algorithm called Pulse Decomposition Analysis (PDA) [ 3 ]. It is based on the concept that five individual component pressure pulses constitute the peripheral arterial pressure pulse.…”
Section: Introductionmentioning
confidence: 99%
“…The object of this work is to validate a new approach to tracking central blood pressure. The approach, based on Pulse Decomposition Analysis (PDA), [ 17 ] integrates and further develops the findings of a number of studies that have confirmed the existence of two major reflection sites in the central arteries [ 18 , 19 ]. The first reflection site is the juncture between thoracic and abdominal aorta, which is marked by a significant decrease in diameter and a significant change in elasticity.…”
Section: Introductionmentioning
confidence: 99%